Connecting Crises: Young People in Nepal Reflecting on Life Course Transitions and Trajectories during Times of Uncertainty - Adrian A. Khan (MDPI AG, 2021)
During certain crises, displacement of populations seeking safe refuge elsewhere can occur without the certainty of a return, if at all. Children and young people in such contexts often face the additional challenge of restrictions or disregard towards engaging their agency in migration decision-making processes. Through 60 in-depth interviews with 30 trans-Himalayan participants (ages of 16–23) and multi-sited ethnography throughout Nepal, this paper investigates multiple experiences of crises experienced by young people and the effects on their life course trajectories. From focusing on the Civil War in 1996–2006, the 2015 earthquake, and most recently the COVID-19 pandemic, this paper proposes that initial displacements from the Civil War, when connected with other crises later on in a participant’s life course, better prepared them to deal with crises and enabled them to create a landscape of resilience. Furthermore, a landscape of resilience that connects past and present life course experiences during crises prepared some participants for helping their larger communities alleviate certain crises-related tension. Overall, this paper extends analysis on an under-researched group of young migrants by connecting crises that shaped their (im)mobility and life trajectories, rather than approaching crises as singular, isolated experiences.